Determinants of facility-based childbirth among adolescents and young women in Guinea: A secondary analysis of the 2018 Demographic and Health Survey. - Fassou Mathias Grovogui; Lenka Benova; Hawa Manet; Sidikiba Sidibe; Nafissatou Dioubate; Bienvenu Salim Camara; Abdoul Habib Beavogui; Alexandre Delamou (Public Library of Science (PLoS), 2022)
Introduction Maternal mortality remains very high in Sub-Saharan African countries and the risk is higher among adolescent girls. Maternal mortality occurs in these settings mainly around the time of childbirth and the first 24 hours after birth. Therefore, skilled attendance in an enabling environment is essential to reduce the occurrence of adverse outcomes for both women and their children. This study aims to analyze the determinants of facility childbirth among adolescents and young women in Guinea. Methods We used the Guinea Demographic and Health Survey (DHS) conducted in 2018. All females who were adolescents (15-19) or young women (20-24 years) at the time of their most recent live birth in the five years before the survey were included. We examined the use of health facilities for childbirth and its determinants selected through the Andersen health-seeking model using descriptive analysis and multilevel multivariable logistic regression. All descriptive and analytical estimated were produced by adjusting for the survey sampling using the svy option, including adjustment for clustering, stratification and unequal probability of selection and non-response (individual sample weights). The subpopulation option was also used to account for the variance of estimations. Results Overall, 58% of adolescents and 57% of young women gave birth in a health facility. Young women were more likely to have used private sector facilities compared to adolescents (p<0.001). Factors significantly associated with a facility birth in multivariable regression included: secondary or higher educational level (aOR = 1.86; 95%CI:1.24-2.78) compared to no formal education; receipt of 1-3 antenatal visits (aOR = 9.33; 95%CI: 5.07-17.16) and 4+ visits (aOR = 16.67; 95%CI: 8.82-31.48) compared to none; living in urban (aOR = 2.50; 95%CI: 1.57-3,98) compared to rural areas. Women from poorest households had lower odds of facility-based childbirth. There was substantial variation in the likelihood of birth in a health facility by region, with highest odds in N'Zérékoré and lowest in Labé. Conclusion The percentage of births in health facilities among adolescents and young women in Guinea was 58%. This remains suboptimal regarding the challenges associated maternal mortality and morbidity issues in Guinea. Socio-economic characteristics, region of residence and antenatal care use were the main determinants of its use. Efforts to improve maternal health among this group should target care discontinuation between antenatal care and childbirth (primarily by removing financial barriers) and increasing the demand for facility-based childbirth services in communities, while paying attention to the quality and respectful nature of healthcare services provided there.